Estudo farmacoterapêutico e farmacogenético em crianças e adolescentes com transtorno do déficit de atenção e hiperatividade tratados com metilfenidato - Batista, José Márcio Machado (2016)
Disorder Attention Deficit/Hyperactivity Disorder (ADHD) is considered the neuropsychiatric disorder most common and socially important in children and adolescents. This work it is an observational, descriptive, longitudinal, with a quantitative approach, in patients enrolled in a pharmaceutical care program for ADHD. This study aimed to investigate the use of methylphenidate (MPD) in ADHD therapy in children and adolescents in a Medical Specialty Center, outline the socio-demographic, socioeconomic, pharmacotherapeutic and pharmacogenetic children and adolescents users of MPD, registered in health care facility and to develop a method of chromatographic determination MPD in human plasma samples by separation of racemic MPD by ultra performance liquid chromatography (UPLC), for therapeutic monitoring purposes. Data were collected from form applied to patients and caregivers, and information from medical records and the clinical team (doctor and pharmacist). The pharmacogenetic study of patients involved polymorphisms carboxylesterase gene 1 (CES1) and its correlation with therapeutic response and possible adverse reactions in patients. All patients were followed according to the Dader method, and the drug-related problems (DRP) recorded and categorized as the 2nd Consensus of Granada. It identified a sample of 51 patients. The results showed that most patients were males (86.27%), with a mean age of 12 years and family income less than two minimum wages (72.55%). Regarding the number of drugs used, the majority (54.9%) were in MPD monotherapy. Results showed that prevailed among ADHD patients combined subtype (76%). Adverse events were the main cause of health problems of patients (63.51%), followed by drug interactions (14.87%). The main identified DRP was the security, with adverse reactions such as insomnia and loss of appetite. For genetic testing, a sample of 10 patients with ADHD and alone with MFD agreed to participate in the study, where 40% of children and adolescents, alone with MFD showed heterozygous G / A for variant CES1 p.Gly143Glu that entails less metabolizing MFD. A separation method for enantiomeric MFD ultra performance liquid chromatography (UPLC) was established with retention times of MPD isomers of 7.0 and 8.1 minutes for the Levo-MPD and Dextro-MFD, respectively, such method considered precise and accurate. Our study shows the importance, viability, and effectiveness of pharmaceutical monitoring in the evaluation of the use of methylphenidate in children and adolescents, and points out the need for more research on the aspects of safety and effectiveness related to pharmacotherapy and pharmacogenetic profile that children and adolescents, and its relationship to the short and long-term response, and adverse reactions.